Cockayne syndrome in siblings (clinico-pathological study) - Özdirim, Emire; Tınaztepe, Behçet; Pınar, Tuğrul (The Turkish Journal of Pediatrics, 1981)
Clinical and laboratory data on two siblings aged 8 years and 18 months with Cockayne syndrome are presented, the first cases reported in Turkey. Complete post-mortem examination was performed on the older sibling. Pathologic examination of the brain supports the concept that Cockayne syndrome is a form of sudanophilic leukodystrophy. Although histologic renal lesions were found, the patient presented no clinical symptoms or signs related to the kidney. The significance of the kidney histology remained obscure.
Keywords: Cockayne syndrome; deafness; dwarfism; retinal atrophy; sudanophilic leukodystrophy